Rural households' vulnerability to drought and implications for resilience : Insights from Bushbuckridge, Mpumalanga, South Africa - Rusere, Farirai; Houngué, Nina Rholan; Mkuhlani, Siyabusa; Soropa, Gabriel; Hunter, Lori; Twine, Wayne; Samimi, Cyrus (Progress in Disaster Science, 2026)
The increasing frequency of droughts in southern Africa is placing pressure on resource-dependent populations and constraining their ability to build resilience. This study investigates how rural communities in Bushbuckridge, Mpumalanga, South Africa, perceive and respond to El Niño-induced droughts. Using a mixed-methods approach, including surveys and interviews, this research examines household awareness, sensitivity, and adaptive capacity, as well as the factors shaping these dimensions. The findings show that households with greater climate awareness better recognize the potential impacts of El Niño-related drought on agriculture, livestock, and the local economy. Households with members engaged in local non-farm activities or migrant labor displayed higher adaptive capacity but also greater vulnerability in terms of sensitivity, as reliance on external income often reduced on-farm labor and adaptation efforts. Social networks emerged as both an asset, facilitating the spread of adaptation information, and a liability, sometimes reinforcing misinformation and delaying the uptake of science-based strategies. Gender dynamics also influenced adaptive capacity, with male-headed households generally having more resources and labor to implement adaptation measures. These findings highlight that resilience is not solely determined by material resources but emerges from the interaction of awareness, livelihood diversification, social relations, and gendered access to assets. The study underscores the need for resilience initiatives that strengthen local extension services, improve risk communication, and engage social networks while addressing gendered constraints, in order to support timely, informed, and equitable drought adaptation in rural communities.
Keywords: El Niño; Drought; Extreme weather; Adaptive capacity; Sensitivity; Rural communities